A negative photoresist containing a permeation inhibitor and a method for preparing and using the same

CN122902166APending Publication Date: 2026-10-13JIANGSU AISEN SEMICON MATERIAL CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611288914.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]本发明目的是:提供一种含抗渗透剂的负性光刻胶及其制备方法和应用,以解决现有负性光刻胶在化学镀镍钯金工艺中因化学镀液渗透而导致渗镀和膜层脱落的问题,进一步解决在高温碱性化学镀液中光刻胶膜层尺寸稳定性不足导致图形精度下降的问题

Benefits of technology

(1)通过添加六甲氧基三聚氰胺甲醛树脂至配方后,其六个甲氧基在固化过程中与丙烯酸树脂的羧基、羟基以及交联剂的活性基团发生交联反应,在交联过程中形成密集的化学键位点,缩小了分子链之间的自由体积,降低了化学镀液中小分子组分的扩散系数。实验验证表明,实施例1-3中含抗渗透剂的光刻胶在化学镀镍钯金工艺后均未发生渗镀,光刻胶覆盖区域未见金属沉积;而未添加抗渗透剂的对比例1-3均出现渗镀现象。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122902166A_ABST
    Figure CN122902166A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of photoresist materials, in particular to a negative photoresist containing an anti-permeation agent and a preparation method and application thereof. The preparation raw materials of the negative photoresist include 18-30 parts of acrylic resin, 3-5 parts of a photo initiator, 14-28 parts of a crosslinking agent, 35-55 parts of a solvent, 2-4 parts of an anti-permeation agent and 200-500 ppm of an auxiliary agent; the anti-permeation agent is hexamethoxymethyl melamine formaldehyde resin; the acrylic resin is prepared by free radical polymerization of methyl methacrylate, isoprene, isobornyl acrylate, hydroxyethyl methacrylate and glycidyl methacrylate; and the crosslinking agent is at least one selected from 1,4-butanediol diacrylate, ethoxylated trimethylolpropane triacrylate and bistrimethylolpropane tetraacrylate. When the negative photoresist is used as an anti-plating mask in a chemical nickel-palladium-gold plating process, the negative photoresist can resist the penetration of a chemical plating solution and a high-temperature alkaline environment, and does not have the phenomena of colloid falling off and permeation plating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photoresist materials technology, specifically to a negative photoresist containing an anti-permeation agent, its preparation method, and its application. Background Technology

[0002] In semiconductor packaging and high-end printed circuit board manufacturing, electroless nickel-palladium-gold (ENEPIG) plating is a key surface treatment technology. This technology significantly improves solder joint reliability by sequentially depositing a nickel layer as a diffusion barrier, a palladium layer as an antioxidant, and a gold layer as a solder / bonding layer on a copper surface. In the fabrication of fine lines with micron-level line spacing, negative photoresists, acting as anti-plating masks, are needed to protect non-target areas from metal deposition during electroless plating. Negative photoresists cross-link and cure in exposed areas, while unexposed areas are developed and removed. Due to their excellent masking ability and mechanical strength, they are widely used in electroplating and electroless plating processes.

[0003] Traditional processes typically involve first forming copper traces on a substrate, followed by electroless plating. However, as electronic products move towards higher density and finer pitch, the "trace-then-plating" approach faces challenges. At micron-level line spacing, full-board electroless plating can easily lead to metal residue in non-target areas, reducing insulation. To address this issue, existing technologies often employ "plating-then-trace" or "mask-stripping" processes, but the negative photoresist used in these processes presents the following problems in electroless nickel-palladium-gold plating: First, the penetration ability of electroless nickel plating solutions is insufficient. Electroless nickel plating solutions contain reducing agents, such as sodium hypophosphite, complexing agents, and various additives, which are highly corrosive. The cross-linked network of traditional photoresist after curing has limited density, allowing small-molecule plating solution components to slowly penetrate into the film layer or diffuse along the interface, causing "diffusion plating" or a decrease in film-substrate adhesion.

[0004] Second, the dimensional stability is poor under high temperature and humidity conditions. Electroless nickel plating is usually carried out at 80-90°C for several tens of minutes. Under these conditions, the photoresist film may undergo thermal expansion, plastic deformation, or even partial decrosslinking, leading to collapse of the pattern sidewalls or changes in the size of the masking openings, ultimately affecting the pattern accuracy of the deposited metal.

[0005] Therefore, there is an urgent need to develop a negative photoresist that can maintain structural integrity and passivation capabilities in harsh chemical environments such as electroless nickel plating (high temperature and strong alkali), electroless palladium plating, and immersion gold, and withstand the penetration of electroless plating solutions without diffusion or film peeling, thus achieving "templative" direct metal deposition. Summary of the Invention

[0006] The purpose of this invention is to provide a negative photoresist containing an anti-penetration agent, its preparation method, and its application, so as to solve the problem of seepage and film peeling caused by the penetration of the chemical plating solution in the existing negative photoresist in the electroless nickel-palladium-gold plating process, and further solve the problem of insufficient dimensional stability of the photoresist film in high-temperature alkaline chemical plating solution, which leads to a decrease in pattern accuracy.

[0007] The technical solution of the present invention is as follows: In a first aspect, a negative photoresist containing an anti-permeation agent is provided, wherein, by mass parts, the raw materials for preparing the negative photoresist include the following components: 18-30 parts of acrylic resin; 3-5 parts of photoinitiator; Crosslinking agent 14-28 parts; Solvent 35-55 parts; 2-4 parts of anti-permeability agent; Additives 200-500 ppm; The anti-permeation agent is hexamethoxymelamine-formaldehyde resin, which is used to prevent the chemical plating solution from penetrating into the photoresist film layer. The acrylic resin is prepared by free radical polymerization of monomer raw materials containing methacrylic acid, isoprene, isobornyl acrylate, hydroxyethyl methacrylate and glycidyl methacrylate. The crosslinking agent is selected from at least one of 1,4-butanediol diacrylate, ethoxylated trimethylolpropane triacrylate, and bis(trimethylolpropane)tetraacrylate.

[0008] Preferably, the photoinitiator is at least one selected from 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, 2,4-diethylthioxanthone, and 1,2'-bis(2-chlorophenyl)-tetraphenylbiimidazole.

[0009] Preferably, the solvent is propylene glycol methyl ether acetate.

[0010] Preferably, the additives include leveling agents and polymerization inhibitors.

[0011] Preferably, the leveling agent is polyether-modified polydimethylsiloxane, and the polymerization inhibitor is 4-tert-butylcatechol.

[0012] Preferably, the acrylic resin is prepared by the following method: Methacrylic acid, isoprene, isobornyl acrylate, hydroxyethyl methacrylate, glycidyl methacrylate, and propylene glycol methyl ether acetate were added to a reaction vessel and heated to 80–90°C for 6–8 hours under nitrogen protection. After cooling, deionized water was added dropwise to precipitate the product. The precipitate was separated, washed with cyclohexane and propylene glycol methyl ether acetate, and dried to obtain the acrylic resin.

[0013] Preferably, the crosslinking agent is a combination of 1,4-butanediol diacrylate, ethoxylated trimethylolpropane triacrylate, and bis(trimethylolpropane)tetraacrylate.

[0014] In a second aspect, a method for preparing the negative photoresist containing an anti-permeation agent as described in any one of the above claims is provided, comprising the following steps: The acrylic resin, photoinitiator, crosslinking agent, anti-permeability agent, additives and solvent are mixed and stirred until fully dissolved to obtain the negative photoresist.

[0015] Thirdly, the application of the negative photoresist containing an anti-penetration agent as described in any of the above-mentioned methods as an anti-plating mask in electroless nickel-palladium-gold plating processes is provided.

[0016] Compared with the prior art, the advantages of the present invention are: (1) By adding hexamethoxymelamine-formaldehyde resin to the formulation, its six methoxy groups undergo cross-linking reactions with the carboxyl and hydroxyl groups of acrylic resin and the active groups of the cross-linking agent during the curing process. During the cross-linking process, dense chemical bond sites are formed, reducing the free volume between molecular chains and lowering the diffusion coefficient of small molecule components in the electroless plating solution. Experimental verification shows that the photoresists containing anti-permeation agents in Examples 1-3 did not undergo plating penetration after electroless nickel-palladium-gold plating, and no metal deposition was observed in the photoresist-covered area; while comparative examples 1-3 without anti-permeation agents all showed plating penetration.

[0017] (2) The melamine ring structure contained in the hexamethoxymelamine-formaldehyde resin molecule has high rigidity and thermal stability. When 2-4 parts are embedded in the gaps of the cross-linking network, they serve as physical cross-linking points, enhancing the overall network's resistance to thermal deformation under high temperature conditions. This allows the film layer to maintain dimensional stability in an 80-90℃ electroless nickel plating solution without thermal expansion or plastic deformation. Experimental verification shows that the photoresists containing anti-permeation agents in Examples 1-3 did not show any colloid detachment after immersion in an 80-90℃ electroless nickel plating solution for 5-10 minutes, and the film morphology was qualified. However, in Comparative Examples 1-3 without anti-permeation agents, colloid detachment occurred, and the film morphology was unqualified.

[0018] (3) Overall effect: Combining the above two aspects, the addition of 2-4 parts of hexamethoxymelamine-formaldehyde resin simultaneously enhances network density and improves thermal stability. The synergistic effect enables the photoresist to withstand the harsh conditions of the entire electroless nickel-palladium-gold plating process. The overall evaluation of Examples 1-3 was qualified, while the overall evaluation of Comparative Examples 1-3 was unqualified. Attached Figure Description

[0019] The present invention will be further described below with reference to the accompanying drawings and embodiments: Figure 1 This is a microscopic morphology image of the strip channel structure of the negative photoresist provided in Example 1 of the present invention after activation and before electroless plating; Figure 2 The image shows the microstructure of the circular micropore array after electroless nickel-palladium-gold plating and before resist removal, provided in Example 1 of the present invention. Figure 3 This is a microscopic morphology image of the circular micropore array after resist removal provided by the negative photoresist in Embodiment 1 of the present invention; Figure 4 The image shows the microstructure of the strip-shaped channel structure of the negative photoresist provided in Comparative Example 1 of this invention after activation and before electroless plating. Figure 5 The image shows the microstructure of the circular micropore array provided in Comparative Example 1 of this invention after electroless nickel-palladium-gold plating and before resist removal. Figure 6 The image shows the microstructure of the circular micropore array after resist removal provided by Comparative Example 1 of this invention. Figure 7 This is a microscopic morphology image of the strip-shaped colloidal structure detached from the negative photoresist provided in Comparative Example 1 of the present invention after activation and before chemical plating. Detailed Implementation

[0020] The present invention will be further described in detail below with reference to specific embodiments: I. Preparation of Acrylic Resin In a reaction flask equipped with a condenser and stirrer, 27 g of methacrylic acid, 6.9 g of isoprene, 21 g of isobornyl acrylate, 26 g of hydroxyethyl methacrylate, 10 g of glycidyl methacrylate, and 75 g of propylene glycol methyl ether acetate were added. The mixture was heated to 85°C under nitrogen protection and stirred for 7 hours. After the reaction was complete, the temperature was lowered to room temperature. 500 g of deionized water was added dropwise to the resulting solution to induce precipitation. The precipitate was filtered and washed successively with cyclohexane and propylene glycol methyl ether acetate. The washed precipitate was placed in a rotary evaporator and evaporated at 60°C for 3 hours. After drying, acrylic resin was obtained.

[0021] II. Preparation and evaluation of negative photoresist.

[0022] Example 1

[0023] This embodiment provides a negative photoresist containing an anti-permeation agent, the raw materials for which include the following components in parts by weight: 29 parts of the prepared acrylic resin were obtained; Crosslinking agent: 14 parts of 1,4-butanediol diacrylate; Anti-permeation agent: 2 parts hexamethoxymelamine-formaldehyde resin; Photoinitiator: 3 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide; Additive: Polyether-modified polydimethylsiloxane / 4-tert-butylcatechol 500ppm; Solvent: 52 parts of propylene glycol methyl ether acetate.

[0024] The above components were added to a reaction vessel at room temperature and stirred until fully dissolved to obtain a homogeneous negative photoresist solution. The viscosity of this photoresist was measured at 25°C using a rotational viscometer to be 1000–2000 mPa·s.

[0025] The prepared negative photoresist was coated onto a 6-inch copper wafer using a coating machine and pre-baked on a hot plate at 105°C for 300 seconds to form a coating with a thickness of approximately 23.0 μm. The obtained coating was then exposed using a SUSS MA6 lithography machine at an exposure dose of 200–500 mJ / cm². After standing for 5 minutes, a 2.38% (w / w) tetramethylammonium hydroxide aqueous solution at 22°C was used as the developer, and development was performed at 22°C for 110 seconds, followed by a 60-second rinse with pure water and drying with nitrogen.

[0026] The copper sheet with the photoresist pattern is subjected to the following pretreatment steps before electroless plating: (1) Alkaline degreasing: Immerse the copper sheet in an alkaline degreasing agent with a pH of 10-12 and a temperature of 40-50℃ for 3-5 minutes to remove oil and organic impurities from the surface of the copper sheet, and then rinse it with pure water 3 times.

[0027] (2) Micro-etching: The copper surface is lightly etched using a sulfuric acid-hydrogen peroxide system to a depth of 0.5-1 μm, so as to form a rough structure on the copper surface to enhance the adhesion between the photoresist and the copper surface. Then, it is rinsed with pure water 2-3 times.

[0028] (3) Activation: Immerse the copper sheet in a special activator at 25-30°C for 1-2 minutes to activate the chemical activity of the copper surface and provide conditions for the subsequent chemical deposition of nickel layer.

[0029] After pretreatment, the copper sheet will undergo the following chemical plating steps in sequence: (4) Electroless nickel plating: The copper sheet is immersed in an electroless nickel plating solution at 80-90°C for 5-10 minutes to form a uniform nickel layer on the surface of the copper sheet in areas not covered with photoresist. The electroless nickel plating solution contains nickel sulfate, sodium hypophosphite, complexing agent and stabilizer.

[0030] (5) Electroless palladium plating: The copper sheet after electroless nickel plating is immersed in electroless palladium plating solution, and a dense palladium layer is generated on the surface of the nickel layer through a displacement reaction.

[0031] (6) Chemical immersion gold: The copper sheet after chemical palladium plating is immersed in chemical gold plating solution, and a gold layer is formed on the surface of the palladium layer through a displacement reaction.

[0032] After electroless plating is completed, the state of the photoresist film layer after electroless nickel-palladium-gold plating is observed under an optical microscope, including whether there is any colloid peeling or plating penetration.

[0033] In this embodiment, the amount of the anti-permeation agent, hexamethoxymelamine-formaldehyde resin (HMMM), added is 2 parts. HMMM molecules contain six methoxy (-OCH3) functional groups. Under heat curing conditions, these methoxy groups can undergo cross-linking reactions with the carboxyl groups (-COOH) and hydroxyl groups (-OH) on the acrylic resin molecular chain, as well as the active groups on the cross-linking agent molecules. Under thermal action, the methoxy groups of HMMM can be converted into active intermediates such as hydroxymethyl (-CH2OH) or methylene ether bridges (-CH2-O-CH2-), which further undergo condensation reactions with the active hydrogen on the acrylic resin and cross-linking agent molecules.

[0034] At an addition of 2 parts, HMMM does not dominate the cross-linking reaction (the cross-linking reaction is mainly completed by 14 parts of 1,4-butanediol diacrylate), but exists in the interstitial spaces of the cross-linking network in a partially reacted and partially embedded manner. HMMM molecules have a relatively large volume, and even if some of its six methoxy groups are unreacted, they can fill the free volume in the cross-linking network through steric hindrance, thereby reducing the diffusion coefficient of small molecule components in the electroless plating solution. Simultaneously, the melamine ring structure in the HMMM molecule has high rigidity and thermal stability, and its embedding in the network interstitial spaces can enhance the thermomechanical stability of the entire cross-linking network under high-temperature conditions. Therefore, 2 parts of HMMM play an anti-permeation role in this invention.

[0035] The evaluation results show that after electroless nickel-palladium-gold plating, no colloid detachment occurred in the photoresist film layer, no plating penetration occurred, the morphology after electroless plating is qualified, and the overall evaluation is qualified.

[0036] Combination Figures 1 to 3 The negative photoresist containing HMMM anti-permeation agent prepared in Example 1 exhibits excellent anti-permeation properties in the electroless nickel-palladium-gold plating process. For example... Figure 1 As shown, after activation and before electroless plating, the edges of the strip-shaped channel structure are smooth and clear, with no abnormalities observed; Figure 2 As shown, after the electroless nickel-palladium-gold plating process and before resist removal, the edges of the circular micro-orifice array are sharp, the photoresist film layer remains intact, and no resist detachment occurs. The electroless metal plating layer is selectively deposited only on the copper surface area not covered by photoresist, and no non-selective plating is observed. Figure 3As shown, the holes were clean and had uniform gray levels after resist removal, further confirming that the electroless plating solution did not penetrate into the photoresist film layer. This indicates that the HMMM anti-penetration agent added in this invention effectively blocked the penetration of the electroless plating solution, ensuring the masking function of the photoresist.

[0037] Example 2

[0038] This embodiment provides a negative photoresist containing an anti-permeation agent, the raw materials for which include the following components in parts by weight: 24 parts of the prepared acrylic resin; Crosslinking agent: 19 parts of ethoxylated trimethylolpropane triacrylate; Anti-permeation agent: 3 parts hexamethoxymelamine-formaldehyde resin; Photoinitiator: 4 parts of 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone; Additive: Polyether-modified polydimethylsiloxane / 4-tert-butylcatechol 400ppm; Solvent: 48 parts of propylene glycol methyl ether acetate.

[0039] The above components were added to a reaction vessel at room temperature and stirred until fully dissolved to obtain a homogeneous negative photoresist solution. The viscosity of this photoresist was measured at 25°C using a rotational viscometer to be 1000–2000 mPa·s.

[0040] The photoresist of Example 2 was evaluated using the same coating, exposure, development, pretreatment, and electroless nickel-palladium-gold electroless plating process conditions as in Example 1. After electroless plating, the state of the photoresist film was observed under an optical microscope.

[0041] Example 3

[0042] This embodiment provides a negative photoresist containing an anti-permeation agent, the raw materials for which include the following components in parts by weight: 18 parts of the prepared acrylic resin were obtained; Crosslinking agent: 28 parts of bis(trimethylolpropane)tetraacrylate; Anti-permeation agent: 4 parts hexamethoxymelamine-formaldehyde resin; Photoinitiator: 5 parts of 1,2′-bis(2-chlorophenyl)-tetraphenylbiimidazole; Additive: Polyether-modified polydimethylsiloxane / 4-tert-butylcatechol 200ppm; Solvent: 45 parts of propylene glycol methyl ether acetate.

[0043] The above components were added to a reaction vessel at room temperature and stirred until fully dissolved to obtain a homogeneous negative photoresist solution. The viscosity of this photoresist was measured at 25°C using a rotational viscometer to be 1000–2000 mPa·s.

[0044] The photoresist of Example 3 was evaluated using the same coating, exposure, development, pretreatment, and electroless nickel-palladium-gold electroless plating process conditions as in Example 1. After electroless plating, the state of the photoresist film was observed under an optical microscope.

[0045] The evaluation results show that the microstructure test results of Examples 2 and 3 are basically the same as those of Example 1, and no plating or colloid peeling phenomenon was observed.

[0046] Comparative Example 1 This comparative example provides a negative photoresist, the raw materials of which include the following components in parts by weight: 30 parts of the prepared acrylic resin; Crosslinking agent: 15 parts of 1,4-butanediol diacrylate; Photoinitiator: 3 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide; Additive: Polyether-modified polydimethylsiloxane / 4-tert-butylcatechol 500ppm; Solvent: 52 parts of propylene glycol methyl ether acetate.

[0047] The difference from Example 1 is that no anti-permeability agent is added.

[0048] The above components were added to the reaction vessel at room temperature and stirred until fully dissolved to obtain a negative photoresist solution.

[0049] The photoresist of Comparative Example 1 was evaluated using the same coating, exposure, development, pretreatment, and electroless nickel-palladium-gold electroless plating process conditions as in Example 1. After electroless plating, the state of the photoresist film was observed under an optical microscope.

[0050] The evaluation results showed that after electroless nickel-palladium-gold plating, the photoresist film layer experienced colloid detachment and plating penetration, resulting in an unqualified morphology after electroless plating. The overall evaluation was deemed unqualified.

[0051] Combination Figures 4 to 7 In Comparative Example 1, without the addition of HMMM anti-permeation agent, defects such as plating penetration and film peeling occurred during the electroless nickel-palladium-gold plating process. Figure 4 As shown, after activation but before electroless plating, the edges of the strip-shaped channel structure showed slight blurring, indicating that the electroless plating solution had begun to diffuse along the interface; as Figure 5 As shown, after electroless plating and before resist removal, a distinct dark halo appeared at the edge of the circular micropore array, indicating non-selective plating penetration. Figure 6 As shown, metal residue was found on the hole walls after adhesive removal, confirming that the plating had penetrated deep into the film layer; more seriously, as... Figure 7 As shown, in the strip-shaped structure after activation and before electroplating, obvious wavy peeling marks appeared at the bottom of the photoresist film layer, that is, the colloid detached.

[0052] The above results indicate that, due to the lack of an anti-penetration agent, the chemical plating solution easily penetrates into the interior of the photoresist film or diffuses along the interface, causing the photoresist's anti-plating masking function to completely fail.

[0053] Comparative Example 2 This comparative example provides a negative photoresist, the raw materials of which include the following components in parts by weight: 25 parts of the prepared acrylic resin; Crosslinking agent: 21 parts of ethoxylated trimethylolpropane triacrylate; Photoinitiator: 4 parts of 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone; Additive: Polyether-modified polydimethylsiloxane / 4-tert-butylcatechol 400ppm; Solvent: 48 parts of propylene glycol methyl ether acetate.

[0054] The difference from Example 2 is that no anti-permeability agent is added.

[0055] The above components were added to the reaction vessel at room temperature and stirred until fully dissolved to obtain a negative photoresist solution.

[0056] The photoresist of Comparative Example 2 was evaluated using the same coating, exposure, development, pretreatment, and electroless nickel-palladium-gold electroless plating process conditions as in Example 1. After electroless plating, the state of the photoresist film was observed under an optical microscope.

[0057] Comparative Example 3 This comparative example provides a negative photoresist, the raw materials of which include the following components in parts by weight: 20 parts of the prepared acrylic resin; Crosslinking agent: 30 parts of bis(trimethylolpropane)tetraacrylate; Photoinitiator: 5 parts of 1,2′-bis(2-chlorophenyl)-tetraphenylbiimidazole; Additive: Polyether-modified polydimethylsiloxane / 4-tert-butylcatechol 200ppm; Solvent: 45 parts of propylene glycol methyl ether acetate.

[0058] The difference from Example 3 is that no anti-permeability agent is added.

[0059] The above components were added to the reaction vessel at room temperature and stirred until fully dissolved to obtain a negative photoresist solution.

[0060] The photoresist of Comparative Example 3 was evaluated using the same coating, exposure, development, pretreatment, and electroless nickel-palladium-gold electroless plating process conditions as in Example 1. After electroless plating, the state of the photoresist film was observed under an optical microscope.

[0061] The evaluation results show that the microstructure test results of Comparative Example 2 and Comparative Example 3 are basically consistent with those of Comparative Example 1, and all of them show varying degrees of plating penetration and colloid peeling.

[0062] III. Summary of Evaluation Results The negative photoresists of Examples 1-3 and Comparative Examples 1-3 were evaluated according to the above method. The evaluation items included: whether the photoresist film layer experienced colloid detachment after electroless plating, whether plating diffusion occurred, and whether the film morphology after electroless plating was qualified. The evaluation results are summarized in Table 1.

[0063] Table 1: Formulation composition and evaluation results of Examples 1-3 and Comparative Examples 1-3

[0064] In Table 1, the units for acrylic resin, crosslinking agent, antipermeation agent, photoinitiator, and solvent are parts by mass, and the units for additives are ppm. The acrylic resin is a pre-prepared acrylic resin; the crosslinking agents are 1,4-butanediol diacrylate (Example 1, Comparative Example 1), ethoxylated trimethylolpropane triacrylate (Example 2, Comparative Example 2), and bis(trimethylolpropane tetraacrylate) (Example 3, Comparative Example 3); the photoinitiators are 2,4,6-trimethylbenzoyl diphenylphosphine oxide (Example 1, Comparative Example 1), 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone (Example 2, Comparative Example 2), and 1,2′-bis(2-chlorophenyl)-tetraphenylbiimidazole (Example 3, Comparative Example 3); the antipermeation agent is hexamethoxymelamine-formaldehyde resin; the additives are a mixture of polyether-modified polydimethylsiloxane and 4-tert-butylcatechol; and the solvent is propylene glycol methyl ether acetate.

[0065] The evaluation results in Table 1 show that: In Examples 1-3, by adding 2-4 parts of hexamethoxymelamine-formaldehyde resin as an anti-permeation agent to the negative photoresist formulation, the prepared photoresists did not exhibit colloid shedding or plating phenomena after electroless nickel-palladium-gold plating. The morphology of the film layer after electroless plating was qualified, and the overall evaluation was qualified.

[0066] In Comparative Examples 1 to 3, without the addition of an anti-permeation agent, the photoresists prepared all exhibited colloid detachment and plating phenomena after electroless nickel-palladium-gold plating. The morphology of the film layer after electroless plating was unqualified, and the overall evaluation was unqualified.

[0067] In summary, adding hexamethoxymelamine-formaldehyde resin as an anti-permeation agent to the negative photoresist formulation, in combination with acrylic resin of a specific composition and a specific crosslinking agent, can improve the photoresist film's resistance to electroless plating solution penetration and its structural stability under high temperature and humidity conditions, preventing colloid shedding and plating penetration.

[0068] The above embodiments are merely illustrative of the technical concept and features of the present invention, intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly, and should not be construed as limiting the scope of protection of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects. The scope of the present invention is defined by the appended claims rather than the foregoing description, and thus all changes falling within the meaning and scope of the equivalents of the claims are intended to be included within the present invention.

Claims

1. A negative photoresist containing an anti-permeation agent, characterized in that, The raw materials for preparing the negative photoresist, by weight, include the following components: 18-30 parts of acrylic resin; 3-5 parts of photoinitiator; Crosslinking agent 14-28 parts; Solvent 35-55 parts; 2-4 parts of anti-permeability agent; Additives 200-500 ppm; The anti-permeation agent is hexamethoxymelamine-formaldehyde resin, which is used to prevent the chemical plating solution from penetrating into the photoresist film layer. The acrylic resin is prepared by free radical polymerization of monomer raw materials containing methacrylic acid, isoprene, isobornyl acrylate, hydroxyethyl methacrylate and glycidyl methacrylate. The crosslinking agent is selected from at least one of 1,4-butanediol diacrylate, ethoxylated trimethylolpropane triacrylate, and bis(trimethylolpropane)tetraacrylate.

2. The negative photoresist containing an anti-permeation agent according to claim 1, characterized in that, The photoinitiator is at least one selected from 2,4,6-trimethylbenzoyl diphenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, 2,4-diethylthioxanthone, and 1,2'-bis(2-chlorophenyl)-tetraphenylbiimidazole.

3. The negative photoresist containing an anti-permeation agent according to claim 1, characterized in that, The solvent is propylene glycol methyl ether acetate.

4. The negative photoresist containing an anti-permeation agent according to claim 1, characterized in that, The additives include leveling agents and polymerization inhibitors.

5. The negative photoresist containing an anti-permeation agent according to claim 4, characterized in that, The leveling agent is polyether-modified polydimethylsiloxane, and the polymerization inhibitor is 4-tert-butylcatechol.

6. The negative photoresist containing an anti-permeation agent according to claim 1, characterized in that, The acrylic resin is prepared by the following method: Methacrylic acid, isoprene, isobornyl acrylate, hydroxyethyl methacrylate, glycidyl methacrylate, and propylene glycol methyl ether acetate were added to a reaction vessel and heated to 80–90°C for 6–8 hours under nitrogen protection. After cooling, deionized water was added dropwise to precipitate the product. The precipitate was separated, washed with cyclohexane and propylene glycol methyl ether acetate, and dried to obtain the acrylic resin.

7. The negative photoresist containing an anti-permeation agent according to claim 1, characterized in that, The crosslinking agent is a combination of 1,4-butanediol diacrylate, ethoxylated trimethylolpropane triacrylate, and bis(trimethylolpropane)tetraacrylate.

8. A method for preparing a negative photoresist containing an anti-permeation agent as described in any one of claims 1 to 7, comprising the following steps: The acrylic resin, photoinitiator, crosslinking agent, anti-permeability agent, additives and solvent are mixed and stirred until fully dissolved to obtain the negative photoresist.

9. The application of the negative photoresist containing an anti-penetration agent according to any one of claims 1 to 7 as an anti-plating mask in the electroless nickel-palladium-gold plating process.